2020
DOI: 10.1007/s12072-020-10098-y
|View full text |Cite
|
Sign up to set email alerts
|

Ropeginterferon alfa-2b every 2 weeks as a novel pegylated interferon for patients with chronic hepatitis B

Abstract: Background Ropeginterferon alfa-2b is a novel mono-pegylated interferon that has only one major form as opposed to 8–14 isomers of other on-market pegylated interferon, allowing injection every two or more weeks with higher tolerability. It received European Medicines Agency and Taiwan marketing authorization in 2019 and 2020, for treatment of polycythemia vera. This phase I/II study aimed to have preliminary evaluation of safety and efficacy in chronic hepatitis B. Methods Thirty-one HBeAg-positive and 31 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 26 publications
2
41
0
Order By: Relevance
“…Although PEG‐IFN was removed from current HCV treatment guidelines, ropeginterferon alfa‐2b is still the backbone of treatment for CHB or chronic hepatitis D (CHD), due to its antiviral mechanisms, which include direct inhibition of viral replication and the modulation of immune response. In our phase I/II study in CHB patients, ropeginterferon alfa‐2b showed comparable safety profile and better HBeAg seroconversion rate than PEG‐IFN alfa‐2a 2 . There are several approved treatments including PEG‐IFN, nucleoside analogues (lamivudine, entecavir, and telbivudine), and nucleotide analogues (adefovir dipivoxil, tenofovir disoproxil fumarate, and tenofovir alafenamide) in CHB.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Although PEG‐IFN was removed from current HCV treatment guidelines, ropeginterferon alfa‐2b is still the backbone of treatment for CHB or chronic hepatitis D (CHD), due to its antiviral mechanisms, which include direct inhibition of viral replication and the modulation of immune response. In our phase I/II study in CHB patients, ropeginterferon alfa‐2b showed comparable safety profile and better HBeAg seroconversion rate than PEG‐IFN alfa‐2a 2 . There are several approved treatments including PEG‐IFN, nucleoside analogues (lamivudine, entecavir, and telbivudine), and nucleotide analogues (adefovir dipivoxil, tenofovir disoproxil fumarate, and tenofovir alafenamide) in CHB.…”
Section: Discussionmentioning
confidence: 82%
“…However, increased pulmonary AEs were reported in the phase 3 trial and the project was discontinued in 2010 22 . In contrast, no lung toxicities was observed in ropeginterferon alfa‐2b use, up to totally 629 patients, including 102 healthy subjects, 313 patients with CHB or C, and 214 PV patients 1–3 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations